Renaming of three recently described eels of the genus Neenchelys (Teleostei: Anguilliformes: Ophichthidae) from the western Pacific - Ho, Hsuan-Ching; Mccosker, John E.; Smith, David G. (Zootaxa, 2015)
In our earlier paper (Ho et al., 2013), we described three new species of the eel genus Neenchelys Bamber, 1915. Unfortunately, the critical step of registering the work in ZooBank was omitted, thus rendering the names unavailable. In this paper, we present abbreviated descriptions of the new species in order to make these names available in accordance with the amended Article 8.5 of the International Code of Zoological Nomenclature.